Stent-Graft Migration Post-Endovascular Repair of Thoracic Aorta: A Retrospective Cohort Study - Amit Ajit Deshpande; Niraj Nirmal Pandey; Manish Shaw; Sanjeev Kumar; Priya Jagia; Sanjiv Sharma; Shiv Choudhary (Indian Journal of Radiology and Imaging, 2022)
Background Migration of the stent-graft post-thoracic endovascular aortic repair (TEVAR) is not uncommon; however, it is sparsely reported. The objective of this study was to assess the incidence, risk factors, and complications of stent-graft migration post-TEVAR. Materials and Methods Thirty-one patients who underwent TEVAR were retrospectively analyzed. The demographic, anatomical, and procedure-related factors were assessed. The measurements were done along the greater curvature of aorta around two fixed anatomic landmarks, that is, left common carotid artery or neoinnominate artery (hybrid repair) proximally and celiac artery distally. Aortic elongation and migration at proximal, distal, as well as at overlapping zone were measured. More than 10 mm of migration was considered significant. Results Significant migration was observed in six (19%) patients. No significant migration was observed in the overlapping zone. The proximal landing zone 3 (odds ratio [OR] 12.78, p 0.01) was a significant risk factor, whereas landing zone 2 was a protective factor against the migration (OR 0.08, p 0.02). The odds for migration were more in segments I/3 and II/3 compared with I/2 and II/2, respectively, as per Modified Arch Landing Areas Nomenclature. A single complication was seen in the migration group which was treated by an overlapping stent graft. Conclusion The stent-graft migration after TEVAR is not uncommon. Type 3 proximal landing zone was a significant risk factor for migration with an increased risk toward I/3 and II/3. Proximal landing zone 2 as well as adequate overlapping distance in multiple stent grafts can prevent migration. Ethical Approval No IECPG-227/24.06.2020